Verrucous carcinoma of the bladder with koilocytosis unassociated with vesical schistosomiasis - Fabio Lewin; Ana Paula Garcia Cardoso; Lucíla Heloísa Simardi; Marcos Tobias Machado (São Paulo Medical Journal)
CONTEXT: Verrucous carcinoma of the bladder is a very rare malignant neoplasm, histologically similar to condyloma acuminatum. Usually it shows association with vesical schistosomiasis (bilharziasis). Only 13 cases unrelated to bilharziasis have been reported to date, and none of them reported koilocytosis, a typical finding in human papillomavirus infection. CASE REPORT: We report a case of verrucous carcinoma of the bladder that was unrelated to bilharziasis, with koilocytosis and absence of human papillomavirus. The literature relating to the topic is discussed.